Association between social support and depressive symptoms among Chinese nurses with formal employment versus contract-based employment - Fu, Chang; Cui, Xuedan; Geng, Lei; Cao, Fenglin (Frontiers in Psychiatry, 2023)
Background Inequalities may exist in social and health status among nurses with different employment types. Few studies have investigated the relationship between social support and depressive symptoms among formally employed nurses compared with those in contract-based employment. This study aimed to examine the associations between social support and depressive symptoms among Chinese nurses with different forms of employment. Methods The present cross-sectional study was performed with 1,892 nurses from 12 tertiary hospitals in Shandong Province, China. The Social Support Rating Scale and the 10-item Center for Epidemiologic Studies Depression Scale were used to measure social support and depressive symptoms, respectively. The association between social support and depressive symptoms among participants was explored using multiple linear regression analysis. Results The prevalence of depressive symptoms was 45.7%. The mean score for total social support was 40.16 (SD = 7.47), which was lower than the norms in the general Chinese population. Formally employed participants’ total social support scores were statistically significantly higher than those of contract-based employees (p ≤ 0.05). After controlling for confounding factors, the multiple linear regression analysis showed that subjective support and support utilization scores were inversely associated with depressive symptoms. Objective support scores were negatively associated with depressive symptoms only among contract-employment nurses. Conclusion Chinese nurses have a higher prevalence of depressive symptoms and lower social support than the Chinese general population. Compared with contract-employment nurses, formally employed nurses had higher social support. Inverse associations exist between social support and depressive symptoms among nurses with different types of employment. It is suggested that improving Chinese nurses’ social support levels and reducing their depressive symptoms, especially for nurses employed through contracts, are critical.